2020
DOI: 10.21462/jeltl.v5i2.407
|View full text |Cite
|
Sign up to set email alerts
|

The Dominant Speech Functions in Cigarette Billboard Texts

Abstract: <em>This research related to speech functions in cigarette billboard texts. The objectives are to describe the category and to derive dominantly used and explain the factors of the phenomenon of speech functions. The research method used descriptive qualitative. Data was collected by applying documentary techniques from commercial cigarette billboard texts (headline, subhead, slogan and images) in public places around the city center of Medan. The finding describes of the four speech functions available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Then, it is ended with a period (.) (Cobuild, 2011;Leech, 2003;Carter, 2006;Downing and Locke, 2006;in Batubara and Nasution, 2020;2020a;2020b). In other words, statement form is a declarative or assertive statement intended to provide information in spoken or written language.…”
Section: A Speech Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, it is ended with a period (.) (Cobuild, 2011;Leech, 2003;Carter, 2006;Downing and Locke, 2006;in Batubara and Nasution, 2020;2020a;2020b). In other words, statement form is a declarative or assertive statement intended to provide information in spoken or written language.…”
Section: A Speech Functionsmentioning
confidence: 99%
“…A question form is a process of demanding information within the scheme of interrogative expression, which inquires reply from the listener (Grolier, 1992;Cobuild, 2011;Leech, 2003;Carter, 2006;Downing and Locke, 2006;in Batubara and Nasution, 2020;2020a;2020b). There are three types of questions, such as: (1).…”
Section: A Speech Functionsmentioning
confidence: 99%
“…There were some research that described the types of speech function and interpersonal roles conducted by Ridha (2013), Martanto (2014), Arif (2015), Tritama (2017), Suhartini (2017), Artha (2018), Fajar (2019), Nasution (2019), Batubara (2020), and they focused on analyzing the speech fucntions' use between human in daily life. It showed that there are 10 types of speech functions such as statement, answer, question, acknowledgement, contradiction, command, offer, disclaimer rejection, and acceptance (Martanto, 2014).…”
Section: Introductionmentioning
confidence: 99%